Biocompatible conjugated polymer nanoparticles for highly efficient photoacoustic imaging of orthotopic brain tumors in the second near-infrared window. Issue 6 (4th October 2017) - Guo, Bing; Sheng, Zonghai; Kenry,; Hu, Dehong; Lin, Xiangwei; Xu, Shidang; Liu, Chengbo; Zheng, Hairong; Liu, Bin
Abstract : NIR II conjugated polymer nanoparticles with good biocompatibility, excellent photoacoustic stability and high imaging contrast are formulated, which allows highly efficient imaging of orthotopic brain tumors with a high signal/background ratio and a good penetration depth. Abstract : A new second near-infrared (NIR II) conjugated polymer (CP) was designed and synthesized. The CP nanoparticles have good biocompatibility, excellent photostability and high imaging contrast, and have been successfully used to demonstrate the first example of NIR II photoacoustic imaging of orthotopic brain tumors. In comparison with existing contrast agents for photoacoustic imaging, the NIR II CP nanoparticles showed more efficient skull penetration and a much higher signal/background ratio using a 1064 nm laser.